The Effectiveness of Zirconia Crowns Versus Metal Crowns in Anterior Teeth: In vitro Study - Naji Ahmad Alharethi (Wolters Kluwer Medknow Publications, 2024)
Background: The selection between Zirconia crowns and metal crowns for anterior teeth restorations is pivotal in prosthodontics due to their distinct properties. However, a comprehensive investigation into their effectiveness in anterior tooth restorations is warranted. Materials and Methods: This in vitro study aimed to compare the effectiveness of Zirconia crowns and metal crowns in anterior teeth restorations. A total of thirty extracted human maxillary central incisors were prepared to receive crowns and randomly allocated into two groups: group A, zirconia crowns; and group B, metal crowns. The crowns were fabricated following standardized protocols and cemented onto the prepared teeth. Various tests, including fracture resistance, marginal adaptation, and color-matching assessment, were conducted on the samples. Results: The mean fracture resistance of Zirconia crowns (Group A) was determined to be 320 N (SD ± 25), whereas it was 280 N (SD ± 30) for metal crowns (Group B). Marginal adaptation assessment revealed a mean gap width of 50 microns (SD ± 10) for Zirconia crowns and 70 microns (SD ± 15) for metal crowns. Evaluation of color matching showed a higher percentage of acceptable matches for Zirconia crowns compared to metal crowns. Conclusion: Zirconia crowns exhibited superior fracture resistance, marginal adaptation, and color matching in comparison to metal crowns for anterior teeth restorations. These findings advocate for Zirconia crowns as a more effective choice for restoring anterior teeth, offering both strength and esthetic appeal.